ASSESSMENT OF SUCCESS INDICATORS ASSOCIATED WITH MANUFACTURING IC CHIPS IN INDIAN SEMICONDUCTOR MANUFACTURING INDUSTRY - Singh, Karam Bharat; Misra, Subhas Chandra (PEOPLE: International Journal of Social Sciences, 2024)
Integrated circuit plays a crucial role in reducing the size, increasing the processing speed, and enhancing the dependability on the electronic devices. Notably, the widespread use of these technologies has led to advancements in various sectors, including the communications, healthcare, and automobile industry. This study rank and identifies the critical success indicators associated with the manufacturing IC chips in the Indian semiconductor industry by employing one sample t-test approach. Based on the existing literature, the study investigates sixteen success indicators associated with the manufacturing IC chips in India. In addition, experts from the semiconductor manufacturing organization have validated these factors concerning the Indian semiconductor industry. The research concludes that “Monitor the Time-to-Market (SI7)”, “Enhance Customer Satisfaction (SI13)”, “Assess the Yield Rate (SI11)”, and “Calculate the Return on Investment (ROI) for Cost (SI5)”, are the critical success indicators associated with manufacturing of IC chips, as per the t-test analysis from 152 respondents working in the semiconductor sectors. The findings have multiple implications for businesses and policymaker, and can assist various stakeholders, including global semiconductor companies, domestic manufacturers, and fabless semiconductor firms